Economic Growth Mediates the Effects of Socioeconomic Factors and Reduces Stunting in Indonesia - Maman Sulaeman; Khalid Eltayeb Elfaki (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2026)
Research Originality: This study offers original insights by examining the multifactorial determinants of stunting in Indonesia, with particular focus on the roles of social food assistance, food insecurity, public literacy, unemployment, and economic productivity within a panel data framework. Research Objectives: This study aimed to analyze the effects of social food assistance, food insecurity, public literacy, unemployment, and economic productivity on the prevalence of stunting in Indonesia. Research Methods: This study employs a quantitative approach using panel data for 34 Indonesian provinces from 2018 to 2022. The analysis used regression models to evaluate both direct and indirect relationships among the variables. Empirical Results: The findings indicate that literacy, social food assistance, food security, and economic growth significantly reduce stunting rates. Unemployment does not directly affect stunting, but it does so indirectly through its impact on economic growth. Additionally, literacy, food assistance, and food security positively affect economic growth, whereas unemployment has a minimal direct impact. Economic growth is an important mediating variable for reducing stunting. Implications: These results suggest that reducing stunting in Indonesia requires integrated policies that combine social food assistance with improvements in literacy, food security, and economic development. Policymakers should prioritize cross-sectoral strategies, including nutrition education and economic empowerment, to effectively address stunting. JEL Classification: I5, I38, O15, O18 How to Cite:Sulaeman, M., Elfaky, K.E. (2026). Economic Growth Mediates the Effects of Socioeconomic Factors and Reduces Stunting in Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 15(2), 391-406. https://doi.org/10.15408/sjie.v15i2.50243.